CCNP security IPS 642-627 official cert guide - Burns, David; Adesina, Odunayo; Barker, Keith (Indianapolis, IN : Cisco Press, 2012)
A best-of-breed Cisco exam study guide that focuses specifically on the objectives for the CCNP Security IPS exam. It shares preparation hints and test-taking tips, helping one identify areas of weakness and improve both conceptual knowledge and hands-on skills. Material is presented in a concise manner, focusing on increasing understanding and retention of exam topics.
Includes index.
oif 23/06/15
Loans
Keywords: Computer networks; Telecommunications engineers; Electronic data processing personnel